Carols by glow sticks: a retrospective analysis of Poisons Information Centre data. Issue 11 (10th December 2018) - Cairns, Rose; Brown, Jared A; Dawson, Andrew H; Davis, Wendy; Buckley, Nicholas A
Abstract: Objective: To win a Christmas hamper. We also devised a study of our most festive seasonal poisoning, to demonstrate how hard we are working while everyone else is partying. Design: Retrospective analysis of the New South Wales Poisons Information Centre database, which we searched for exposures to the substance code "Cyalume light sticks/glow toys" from 1 July 2013 to 30 June 2017. Setting: A dimly lit basement with a constantly ringing phone. At the other end of the phone was a highly anxious parent and a luminescent child. Main outcome measures: Number of glow stick exposures, route of exposures, patient demographics and seasonal trends in exposures. Results: There were 2918 glow stick exposures over the 4‐year study period. The vast majority of exposures (94%) were in children aged 14 years and younger. Medical complications were very rare. Glow stick exposures were 4.38 times more likely in December (95% CI, 3.02–6.35; P < 0.001). Statistically significant increases were also observed in October, November, January, February and March. Glow stick exposures were 4.20 times more likely during the holiday period of 1 December to 7 January (95% CI, 3.42–5.15; P < 0.001), 2.52 times more likely over summer (95% CI, 2.12–3.00; P < 0.001), and 1.77 times more likely during school holidays (95% CI, 1.47–2.13; P < 0.001). Conclusions: This epidemic of poisoning is perhaps due to mass seasonal synaesthesia. The lack of any significant adverse consequences highlights the contribution that 50 years of injury prevention has made to everyone having a Merry Christmas and a Happy New Year.